Evaluation of Variants and the Effect of Vaccine on Mortality in Pregnant and Postpartum Women Infected with COVID-19 - Gülçin Hilal Alay; Derful Gülen; Alev Öztaş; Güldem Turan (Galenos Yayinevi, 2023)
Objective:Due to the anatomical, physiological, and immunological changes associated with pregnancy, pregnant women are a population at risk of coronavirus disease-2019 (COVID-19) disease-related morbidity and mortality. There aren't enough studies on the conditions of pregnant and puerperal women who are being followed up in intensive care. The goal of this study was to determine if there was a link between variant status, vaccination status, and mortality in pregnant and puerperal women who were monitored in the intensive care unit during the transition from the alpha to the delta variation.Materials and Methods:The study was designed as a 6-month prospective observational study that occurred between August 1, 2021, and February 1, 2022. Age, present comorbidities, vaccination status, gravida, parity, gestational age (for pregnant women), variant status, birth style (cesarean section or normal delivery), and COVID-19 medical therapies in the critical care unit were all recorded.Results:During the observation period, forty patients were enrolled in the study. The patients average age was 30.9±5.2. The pregnant patients' median gestational week was 32 weeks and 2 days. While 30 of the patients had no concomitant conditions, two had gestational diabetes, four had hypothyroidism, three had chronic hypertension, and one had Wilson's disease. In 37.5% of the patients, intubation was required. During the follow-up in intensive care, ten individuals died. The patients in the intensive care unit spent an average of 12.1±11.8 days there. While 7 (19.4%) of the 36 patients with alpha variants died, 3 (75%) of the 4 patients with delta variants died, a statistically significant difference (p=0.042).Conclusion:In the pregnant population admitted to the intensive care unit, the delta variant was associated with a greater mortality rate. In our research, we discovered that the vaccination rate among pregnant women admitted to the intensive care unit was quite low.